Development and Preliminary Analysis of a VLF-Band Electromagnetic-Wave Observation System for Short-Term Earthquake Precursory Monitoring - Nagao, Toshiyasu; Kamogawa, Masashi; Izutsu, Jun; Suzuki, Tomoyuki; Saito, Airi; Sugiura, Shigeki; Kondo, Hitoshi (Frontiers in Earth Science, 2021)
Preseismic VLF electromagnetic pulses occasionally increase a few days before large earthquakes, especially inland earthquakes. More than two decades ago, the Tokai University group developed a digital recording system for collecting the preseismic electromagnetic pulse data and showed remarkable results. However, due to the limitations of personal computers’ data storage and CPU power during that time, they discontinued the observation. We relaunched this research using current technology. This paper shows the development of the new observation system and presents preliminary results. In addition, we introduce an electromagnetic-wave arrival discrimination algorithm that combines the autoregressive model and the Akaike information criterion, which are commonly used for automatic waveform reading in seismology, to obtain accurate data on the time of arrival (TOA) of electromagnetic waves. Then, source positioning was performed using TOA of electromagnetic waves. Seven electromagnetic pulses near the epicenter were observed 2 days before the largest inland earthquake (M = 5.6) that occurred near the observation network during the observation period (2016–2020). These VLF pulses may be a seismic precursory phenomenon because they were not electromagnetic pulses originating from lightning. These results encourage future observations.